Does Ovariectomy Affect the Mechanics of the Mandibular Alveolar Bone Structure of Wistar Rats Subjected to Tooth Loss and Modified Diet?—A FEA Study - Camila C. Furlan; Alexandre R. Freire; Beatriz C. Ferreira-Pileggi; Luciane N. O. Watanabe; Paulo R. Botacin; Felippe B. Prado; Ana Cláudia Rossi (Biology)
The aim of this study was to evaluate the mechanical effect of ovariectomy, diet, and tooth extraction on the bone structure of the mandible of Wistar rats. Mandibles from 40 female Wistar rats were used, divided into rats with ovariectomy surgery or surgical simulation. Half of the rats had the right upper incisor extracted and a soft diet was introduced for half of the animals for 30 days. After euthanasia, microtomography of the mandibles was performed for bone segmentation to construct three-dimensional models. Each mandible was subjected to a three-point bending test. The simulation by finite element method was configured according to the protocol for positioning the part on the support and force action by the load cell defined in the mechanical tests. Stress dissipation was described qualitatively on a color scale distributed in ranges of stress values. All models showed a higher concentration of stresses in the regions of force action and in the support regions, with differences in stress values and locations. Diet and dental condition interfered in the distribution of stresses, with the lateral surface of the mandible being more influenced by diet and the medial surface of the mandible by diet and dental condition.